Soshiho-Tang, a Traditional Herbal Medicine, Alleviates Atopic Dermatitis Symptoms via Regulation of Inflammatory Mediators - Lee, Ji-Hyun; Jo, Eun Hee; Lee, Bori; Noh, Hyeon Min; Park, Sunggu; Lee, Young-Mi; Kim, Dae-Ki; Park, Min Chel (Frontiers in Pharmacology, 2019)
Soshiho-tang (SST) is a well-known traditional herbal medicine used for the treatment many diseases. The purpose of this study is to investigate the effects of SST on atopic dermatitis (AD) symptoms, and to examine its mechanism. HaCaT cells were stimulated with TNF-α/IFN-γ to induce AD-like keratinocyte environment. 2,4-Dinitrochlorobenzene (DNCB) was used to induce AD-like skin lesions in the dorsal skin of BALB/c mice. SST and dexamethasone were administered orally for 14 day. As a result, SST treatment increased the expression of heme oxygenase-1 (HO-1), an anti-oxidative factor, and the nuclear translocation of NF-E2 p45-related factor 2 (Nrf2). In addition, the treatment also decreased the expression level of inflammatory mediator nuclear factor-κB (NF-κB), and an adhesion molecule intercellular adhesion molecule-1 (ICAM-1). SST treatment (75 and 150 mg/kg) significantly relieved AD symptoms in DNCB-induced AD-like mice by restoring skin thickness, spleen weight, immunoglobulin E (IgE), interleukin 4 (IL-4), pro-inflammatory cytokine expression and expression of several other mediators. We found that SST alleviates AD-like skin lesions and skin inflammation by modulating various atopic symptoms and inflammatory mediators. Therefore, SST can be used as an alternative drug for the treatment of AD.